2020
DOI: 10.1111/cbdd.13758
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming vincristine resistance in cancer: Computational design and discovery of piperine‐inspired P‐glycoprotein inhibitors

Abstract: P-glycoprotein (P-gp)/MDR-1 plays a major role in the development of multidrug resistance (MDR) by pumping the chemotherapeutic drugs out of the cancer cells and reducing their efficacy. A number of P-gp inhibitors were reported to reverse the MDR when co-administered with chemotherapeutic drugs. Unfortunately, none has approved for clinical use due to toxicity issues. Some of the P-gp inhibitors tested in the clinics are reported to have cross-reactivity with CYP450 drug-metabolizing enzymes, resulting in unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…These compounds mostly comprise inhibitors of P-glycoprotein (P-gp) efflux pumps, which can sensitize resistant cells to the correspondent drugs. Vincristine belongs to the drugs, which are efficiently transported from cells via P-gp, and in some cancer cell types overexpressing this efflux pump, leads to strong resistance to vincristine treatment [ 175 ]. The group of Chen et al presented a series of seco-based compounds derived from a previously reported compound praeruptorin A, which potently reverses P-gp-based multidrug resistance.…”
Section: Other Vincristine Combination Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds mostly comprise inhibitors of P-glycoprotein (P-gp) efflux pumps, which can sensitize resistant cells to the correspondent drugs. Vincristine belongs to the drugs, which are efficiently transported from cells via P-gp, and in some cancer cell types overexpressing this efflux pump, leads to strong resistance to vincristine treatment [ 175 ]. The group of Chen et al presented a series of seco-based compounds derived from a previously reported compound praeruptorin A, which potently reverses P-gp-based multidrug resistance.…”
Section: Other Vincristine Combination Therapiesmentioning
confidence: 99%
“…Another example of a P-gp inhibitor, synergizing with vincristine, has been presented by Syed et al, who computationally designed, synthesized, and evaluated two piperine analogs, one of which was proven to potentiate vincristine anticancer activity. This compound was able to reduce vincristine IC 50 in resistant KB cells 24-fold while being inactive in non-resistant cells [ 175 ]. Not only synthetic products but also compounds from natural sources have anti-P-gp activity and were tested in combination with vincristine.…”
Section: Other Vincristine Combination Therapiesmentioning
confidence: 99%
“…44,45 Studies have indicated that targeting P-gp or CSCs is a strategy for the treatment of drug-resistant cancer cells. 15,43 Our results showed that A549/V16 cells had higher expression of P-gp, CD44, and CD133 than A549 cells, suggesting that drug pumping out and CSCs characteristics cause the development of VCR resistance in NSCLC cells. However, PA treatment reduced the expression of these proteins in both cell lines, especially in A549/V16 cells.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that P‐gp overexpression and stemness phenotype are related to resistance to chemotherapy drugs against cancer 15,16 . To determine the effects of PA on drug resistance, the expression of P‐gp and CSCs markers (CD44, CD133, and EpCAM) in PA‐treated cells was detected using immunofluorescence staining and western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation